NMR relaxation rate of a quantum spin chain with an impurity: Магнетизм - Zvyagin, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The relaxation rate of the nuclear magnetic resonance is calculated exactly for a model spin-1/2 chain withthe magnetic impurity. It is shown that the deviations of the impurity's coupling to the chain and the effectiveimpurity's g-factor from the values of the host chain yield special features in the temperature and magnetic fieldbehavior for the relaxation rate.